Factors Affecting the Liquid Workforce in Different Organizations and its Effectiveness - Chakraborty, Debarun; Santra, Adrinil; Dhara, Soumya Kanti (Prabandhan: Indian Journal of Management, 2019)
Background: Ushering in the edge of digital economy has instituted changes in different spheres of people management. Understanding the importance of talent management and the adaptability of employees to various functional domains of the business, corporate houses slowly brought about infusing inescapable changes to keep abreast with the rhythm of future changes. Purpose: The purpose of this study was to determine the relative importance of certain factors that enhance the efficiency of liquid workforce in improving the overall performance of the organization, and it elaborated a practical approach of deploying liquid workforce in improving organizational economy. Design/Methodology: Researchers used descriptive research with cross-sectional design. The study used multiple regression analysis to get the results which were collected from different organizations. Findings: We found from the survey that four factors were mainly influencing liquid workforce and these are : organizations seeking creativity, virtual organizations, flexi-time, and multi-skilled workers, with the last one being the most significant. Research Limitations: This study was conducted in Kolkata with a sample size of 200 respondents taken only from IT, ITES, and telecom organizations. The term 'liquid workforce' is quite new, and respondents had some hesitation during answering questions regarding the same.